Viable Extreme Preterm Birth and Some Neonatal Outcomes in Double Cerclage versus Traditional Cerclage: A Randomized Clinical Trial - Farzaneh Broumand; Fatemeh Bahadori; Tahereh Behrouzilak; Zahra Yekta; Farkhondeh Ashrafi (The Scientific World Journal)
The pregnant women at higher risk of preterm labor, referred to the perinatal clinic of Kosar University Hospital in Urmia district of Iran, were enrolled into a parallel randomized clinical trial. In the investigational arm of the clinical trial, a double cervical cerclage procedure was performed addition to McDonald cerclage. In the control group however, only McDonald cerclage was performed. Extreme preterm labor (GA < 33 weeks) was the primary endpoint of this clinical trial. Age, gestational age at cerclage time, and gravidity were not found to be statistically different between the groups. Means of gestational age were 37.4 and 36.2 weeks, respectively, for the investigational and control groups. The gestational age was 1.2 weeks longer for double cerclage group but the difference was not found to be statistically significant. Preterm birth before 33 weeks of gestation was not experienced by any of the patients who received double cerclage, but five women in control group developed such an extreme preterm labor (𝑃<0.05). The absolute risk reduction in using double cerclage over traditional method was 18 percent (95% confidence interval, 4%–32%). Double cerclage appeared to have higher efficacy than traditional cerclage in preventing preterm labor <33 weeks of gestation.